Iranian women's psychological responses to positive HPV test result: a qualitative study - Kowsar Qaderi; Seyedeh Tahereh Mirmolaei; Mehrnaz Geranmayeh; Shahrzad Sheikh Hasani; Farnaz Farnam (BMC, 2021)
Abstract Background Human papillomavirus testing as an established screenings test allow for the early detection and treatment of cervical cancer. Testing positive for HPV may have adverse consequences for women. This study aimed to explore the psychological impacts of testing positive for HPV on women in a developing country with a distinct cultural and religious background. Methods Qualitative face-to-face semi-structured interviews were conducted with 40 Iranian women who received a positive high-risk HPV result. Content analysis approach was used to data analysis through MAXQDA10. Results Three main categories were emerged: initial confrontation; STD-related psychological burden; and rebuilding health. Initial reactions to positive HPV results were shock, unrealistic fear, confusion, distress, and financial concerns. Stigma was manifested in form of self-blame, fear of HPV-disclosure, negative body image, being stigmatized by healthcare providers, and receiving health care anonymously. Refusal to use insurance services showed how evident and powerful the stigma was. Most women reported lifestyles and sexual behaviors modifications to help their immune system to clear HPV; indicating that the screening can work as a valuable opportunity to improve women's physical and sexual health. Regular follow-up, safe sex and a focus on spirituality enable women infected with HPV to take control of the situation. Worrying about other HPV-linked cancers (oropharynx and anal) and fears of partner infection indicated that women consider HPV to be more than just a cause of cervical cancer. Conclusions The findings implied to the HPV-positive women's need to support and factual information. Designing and implementing interventions that mitigate the psychological effect of positive HPV test results can highlight the potential benefits of screening for women's health.